Atomic Defects in Two‐Dimensional Materials: From Single‐Atom Spectroscopy to Functionalities in Opto‐/Electronics, Nanomagnetism, and Catalysis. Issue 14 (10th March 2017) - Hong, Jinhua; Jin, Chuanhong; Yuan, Jun; Zhang, Ze
Abstract : Two‐dimensional layered graphene‐like crystals including transition‐metal dichalcogenides (TMDs) have received extensive research interest due to their diverse electronic, valleytronic, and chemical properties, with the corresponding optoelectronics and catalysis application being actively explored. However, the recent surge in two‐dimensional materials science is accompanied by equally great challenges, such as defect engineering in large‐scale sample synthesis. It is necessary to elucidate the effect of structural defects on the electronic properties in order to develop an application‐specific strategy for defect engineering. Here, two aspects of the existing knowledge of native defects in two‐dimensional crystals are reviewed. One is the point defects emerging in graphene and hexagonal boron nitride, as probed by atomically resolved electron microscopy, and their local electronic properties, as measured by single‐atom electron energy‐loss spectroscopy. The other will focus on the point defects in TMDs and their influence on the electronic structure, photoluminescence, and electric transport properties. This review of atomic defects in two‐dimensional materials will offer a clear picture of the defect physics involved to demonstrate the local modulation of the electronic properties and possible benefits in potential applications in magnetism and catalysis. Abstract : Single‐atom defects are systematically reviewed in two‐dimensional material systems such as graphene, BN, and transition‐metal dichalcogenides. The local atomic arrangement and associated electronic structure are probed by transmission electron microscopy and single‐atom spectroscopy, and the influence from the defects on the macroscopic functionalities of two‐dimensional materials is discussed, focusing mostly on electronics, photonics, nanomagnetism, and catalysis.